Ferrimagnetic and relaxor ferroelectric properties of R2MnMn(MnTi3)O12 perovskites with R = Nd, Eu, and Gd. Issue 3 (21st December 2020) - Liu, Ran; Tanaka, Masahiko; Mori, Hiromu; Inaguma, Yoshiyuki; Yamaura, Kazunari; Belik, Alexei A.
Abstract : A-site columnar-ordered quadruple perovskites R2 MnMn(MnTi3 )O12 (R = Nd, Eu, Gd) exhibit relaxor-like ferroelectric properties and ferrimagnetic transitions with large moments. Abstract : ABO3 perovskites have a number of ferroelectric instabilities resulting in varieties of long-range and short-range polar distortions. On the other hand, polar distortions are very limited in quadruple perovskites AA′3 B4 O12 and A2 A′A′′B4 O12 . Here we showed that R2 MnMn(MnTi3 )O12 oxides, belonging to a family of A-site columnar-ordered quadruple perovskites, exhibit relaxor-like ferroelectric properties slightly below room temperature. They were synthesized by a high-pressure high-temperature method for R = Nd, Eu, and Gd at about 6 GPa and 1570 K. At room temperature they crystallize in centrosymmetric space group P 42 / nmc (no. 137), and their crystal structures were studied by synchrotron powder X-ray diffraction. They exhibit broad dielectric anomalies just below room temperature with characteristic frequency-dependent features of the relaxor ferroelectric behavior. P – E loop measurements at 77 K confirmed ferroelectricity for R = Nd and Eu. Magnetic and specific heat measurements showed the presence of long-range ferrimagnetic transitions below 20 K (R = Nd), 30 K (R = Eu), and 42 K (R = Gd). Additional specific heat anomalies were observed below about 5 K for R = Nd and Gd probably due to the involvement of rare-earth cations in long-range orderings. The coexistence of ferrimagnetic transitions and relaxor-like ferroelectric properties make R2 MnMn(MnTi3 )O12 perovskites multiferroic materials.